2012
DOI: 10.3892/ol.2012.610
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and apoptosis induction by RNAi with UTMD technology in vitro

Abstract: Abstract. Apoptosis induction by short hairpin RNA (shRNA) expression vectors may be an efficient and promising strategy for cancer gene therapy. Ultrasound-targeted microbubble destruction (UTMD) is an appealing technique; however, there few data are available to demonstrate the feasibility and to optimize the methodology for this technology. The aim of this study was to optimize this technique and to elucidate the effects on gene inhibition and apoptosis induction in vitro. Human cervical cancer cell lines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“… 34 37 At present, a large number of studies have confirmed that UTMD can effectively mediated gene transfer, which has the advantages of safety, practicability and targeting, and is one of the main trends of gene therapy. 38 41 Consistent with our study, one report focused on UTMD-mediated suicide gene and hepatic cancer also demonstrated that the tumor inhibition rate in the treatment group was markedly higher compared with that in the control group. 42 Furthermore, the present study also noted that the in vitro findings were further confirmed via in vivo study.…”
Section: Discussionsupporting
confidence: 89%
“… 34 37 At present, a large number of studies have confirmed that UTMD can effectively mediated gene transfer, which has the advantages of safety, practicability and targeting, and is one of the main trends of gene therapy. 38 41 Consistent with our study, one report focused on UTMD-mediated suicide gene and hepatic cancer also demonstrated that the tumor inhibition rate in the treatment group was markedly higher compared with that in the control group. 42 Furthermore, the present study also noted that the in vitro findings were further confirmed via in vivo study.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies point out the use of low frequency probe can produce a wider and more uniform sound field and that strong cavitation is the key to thrombolysis. However, the optimal parameters have not been formed yet (7). In addition, when MBs exist in the capillaries, ultrasonic irradiation can cause microvascular leakage, intracardiac hemolysis capillary rupture, bleeding, formation, inflammatory cell infiltration, myocardial cell damage and other adverse reactions (7,89,90).…”
Section: Discussionmentioning
confidence: 99%
“…However, the optimal parameters have not been formed yet (7). In addition, when MBs exist in the capillaries, ultrasonic irradiation can cause microvascular leakage, intracardiac hemolysis capillary rupture, bleeding, formation, inflammatory cell infiltration, myocardial cell damage and other adverse reactions (7,89,90). Therefore, more technological revolution should be taken to enhance the biological application of UTMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a large number of proof-of-principle studies have confirmed that ultrasound targeted microbubble destruction (UTMD) could enhance transfection efficiency of naked plasmid DNA by several orders of magnitude [5-7]. Therefore, it is considered as a promising strategy for gene therapy.…”
mentioning
confidence: 99%